Estrategias de mejoramiento del control administrativo y operativo, que contribuyen con el fortalecimiento de los servicios y la satisfacción de los clientes de American Logistics S.A.S. Yumbo (Valle) 2022. (2022)
The main purpose of this degree work is to achieve a significant contribution to the company American Logistics, analyzing each of the causes that generate non-compliance with the promise of service (Quality), through the study of the work and each of the needs detected by the processes of the company in general. Its general objective is to analyze the causes that generate the non-compliance according to the policies that for certification issues must be strictly complied with, to characterize a diagnosis of the processes that allow identifying failures, to determine the taking of times as a work measurement technique and to propose and/or standardize solution schemes to avoid the lack of truthful information in real time